A Proposal of the Improved Method for Measuring Insulation Resistance Between a Photovoltaic Module String and the Earth Using the Self‐Biased Method - Kazama, Takuro; Kato, Kazuhiko (Electrical engineering in Japan, 2025)
ABSTRACT For the safe operation of a photovoltaic generating system, an insulation monitoring function, which can immediately detect deterioration of insulation between photovoltaic module strings and the earth, is indispensable. This function requires accurate measurement, low leakage current, and suppression of rising voltage against the earth. In this paper, a new insulation monitoring method of photovoltaic module strings is proposed by the improved existing self‐biased method (SBM) that has an inevitable voltage rise under measurement. In this new method, both terminals of photovoltaic module strings are always connected to the ground with appropriate resistors. Theoretical discussion and experiments for this new method showed precise measurement and acceptable leakage current under various outdoor conditions. In addition, it was confirmed that this method could sufficiently decrease in the voltage rise compared with the existing SBM.